2017
DOI: 10.1038/s41467-017-00024-6
|View full text |Cite
|
Sign up to set email alerts
|

Near-atomic structure of Japanese encephalitis virus reveals critical determinants of virulence and stability

Abstract: Although several different flaviviruses may cause encephalitis, Japanese encephalitis virus is the most significant, being responsible for thousands of deaths each year in Asia. The structural and molecular basis of this encephalitis is not fully understood. Here, we report the cryo-electron microscopy structure of mature Japanese encephalitis virus at near-atomic resolution, which reveals an unusual “hole” on the surface, surrounded by five encephalitic-specific motifs implicated in receptor binding. Glu138 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
131
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(134 citation statements)
references
References 59 publications
3
131
0
Order By: Relevance
“…Kobayashi and colleagues reported that EGK virus is less virulent compared to EEK due to the former harbouring the VP1-G145 residue, enabling the virus to adsorb more strongly to HS, resulting in attenuated virulence in SCARB2-expressing transgenic mice [56]. Our findings that a strong heparin-binding phenotype attenuates virulence is also observed in other viruses, including Sindbis virus [33], Venezuelan equine encephalitis virus [55], West Nile virus [30], yellow fever virus [31] and Japanese encephalitis virus [57]. Using a monkey model, Zhang et al showed that the establishment of viremia was strongly correlated with EV-A71 neuroinvasion into CNS [16].…”
Section: Discussionmentioning
confidence: 67%
“…Kobayashi and colleagues reported that EGK virus is less virulent compared to EEK due to the former harbouring the VP1-G145 residue, enabling the virus to adsorb more strongly to HS, resulting in attenuated virulence in SCARB2-expressing transgenic mice [56]. Our findings that a strong heparin-binding phenotype attenuates virulence is also observed in other viruses, including Sindbis virus [33], Venezuelan equine encephalitis virus [55], West Nile virus [30], yellow fever virus [31] and Japanese encephalitis virus [57]. Using a monkey model, Zhang et al showed that the establishment of viremia was strongly correlated with EV-A71 neuroinvasion into CNS [16].…”
Section: Discussionmentioning
confidence: 67%
“…Amino-terminal trimethylation of CENP-A, which was identified through high-resolution mass spectrometry, has emerged as a regulator of CENP-A function and is required for precise chromosome segregation during mitosis (Bailey et al 2013; Sathyan et al 2017). Similar to histone H3, the initiating methionine is constitutively removed from CENP-A and the enzyme NRMT1 trimethylates the alpha amino group of the exposed glycine residue on CENP-A (Fig.…”
Section: Role Of Posttranslational Modifications Of Cenp-a In Mitosismentioning
confidence: 99%
“…Chromosome missegregation errors also occur when CENP-A cannot be methylated, but these errors are independent of p53 status. CENP-A methylation mutants leads to uncontrolled cell proliferation, and when expressed in p53 − / − null cells, results in early onset of tumors in nude mice, suggesting that misregulation of CENP-A methylation may have implications in cancer (Sathyan et al 2017). …”
Section: Role Of Posttranslational Modifications Of Cenp-a In Mitosismentioning
confidence: 99%
See 2 more Smart Citations